2009
DOI: 10.32508/stdj.v12i18.2387
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Strength of Steel Fiber Reinforced Concrete

Abstract: Addition of discrete steel fibers to concrete enhances its properties, especially in the areas of serviceability and toughness. In this paper, two semi-empirical methods developed from ACI 318-05 and TCXDVN 356:2005 are proposed to calculate the flexural strength of structures reinforced with both conventional steel bars and steel fibers for analysis and design purposes. The analytical and experimental results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The incorporation of steel fibers into concrete dates back to the 1960s [3]. Studies have shown that the use of steel fibers in concrete enhances the compressive, tensile and flexural strength of SCC [4].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of steel fibers into concrete dates back to the 1960s [3]. Studies have shown that the use of steel fibers in concrete enhances the compressive, tensile and flexural strength of SCC [4].…”
Section: Introductionmentioning
confidence: 99%